A modest 0.5-m rise in sea level will double the tsunami hazard in Macau - Switzer, Adam Douglas (2018)
Rising sea levels will have overwhelmingly negative impacts on coastal communities globally. With previous research focused on how sea-level rise (SLR) affects storm-induced flooding, we show that SLR will also increase both the frequency and the intensity of tsunami-induced flooding, another significant coastal hazard associated with sea-level extremes. We developed probabilistic tsunami inundation maps for Macau, a densely populated coastal city located in the South China Sea, under current sea-level, 0.5-m SLR, and 1-m SLR conditions, using an extensive Monte Carlo tsunami inundation simulation. Our results indicate that conservative amounts of SLR of 0.5 m (by 2060) and 1 m (by 2100) would dramatically increase the frequency of tsunami-induced flooding incidences by a factor of 1.2 to 2.4 and 1.5 to 4.7, respectively.